Assessing the Psychological Effects of Social Isolation on Adolescents During the COVID-19 Pandemic - Elin Andersson; Sofia Nilsson (International Journal of Health and Social Behavior, 2024)
This article examines the psychological effects of prolonged social isolation on adolescents during the COVID-19 pandemic. Utilizing data from mental health surveys and case studies conducted during the pandemic, the research identifies increased levels of anxiety, depression, and loneliness among teenagers as a result of limited social interaction. The study suggests that social isolation during these formative years can have lasting impacts on mental health, emphasizing the importance of support structures for youth during public health crises.,